Antidiarrheal activity of ethanolic bark extract of Mitragyna diversifolia - Jebunnessa, Shaikh Bokhtear Uddin, M. Mahabub- (Bangladesh Pharmacological Society, 2009)
The ethanolic bark extract of Mitragyna diversifolia showed significant (p<0.05) antidiarrheal activity on gastrointestinal motility with barium sulfate milk model and castor oil- induced diarrheal model in rats. These results revealed that the bark extract possess pharmacological activity against diarrhea and may possibly explain the use of the plant in traditional medicine.